Delayed arrival for US baggage screening?. - Bretz, E.A (IEEE spectrum)
The US Department of Transportation (DOT) calculates that 2200 explosives-detecting luggage scanners will be needed to equip all 429 civilian airports in the United States by 31 December 2002, as required by the Aviation and Transportation Security Act passed in the wake of 11 September. But earlier in 2002, when the act's new baggage security rules took effect, only 161 of the machines needed to automatically scan checked baggage had been installed. That means airports have less, than a year to install the other 2039, to be built by just two manufacturers approved by the US Federal Aviation Administration (FAA): InVision Technologies (Newark, Calif.) and L-3 Communications Corp. (New York City). An EDS machine takes a series of X-ray cross-sections of a bag traveling through it on a conveyor belt. As the X-ray machine rotates around the bag, the machine integrates the sections into a near-three-dimensional composite picture, and highlights suspicious objects to be checked manually. This article briefly discusses how the authorities are hedging over the year-end dead-line and how the manufacturers are scrambling to meet the same deadline. Other concerns discusses in the article include finding space for the machines at airports and procedures for getting baggage in and out of the machines